The Influence of Director Characteristics and Company Performances towards Firm Value - Auliarahma Widialvanti; Bernadia Linggar Yekti Nugraheni (Soegijapranata Catholic University, 2024)
This study aims to investigate the influence of director characteristics and company performance towards firm value. There’s a lack of studies about how female director characteristics and company performance affect firm value in Indonesia, therefore this study combined measurements of director characteristics and company performance towards firm value. Using a sample of manufacturing firms listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022, this study applies multiple regression to examine the potential positive associations between director characteristics, company performance, and firm value. Director characteristics are measured by two proxies: the representation of female directors and female educational background, while company performances are assessed by return on assets (ROA) and leverage. Firm value as a dependent variable is represented by Tobin’s Q. The findings indicate a positive association between return on assets and leverage to firm value. However, no evidence is found to support the influence of female representation and educational background towards firm value. Keywords: female_directors, education_background, female_representation, firm_performance, Tobin’s_Q